Aplikasi Kitosan Limbah Udang sebagai Pengawet Ikan Patin (Pangasius sp.) - Zainal Arifin; Prayogi Nugroho (Seminar Nasional Teknik Kimia Kejuangan, 2016)
The shelf life of fresh fish was relatively short. Damage the gills of fish such as color turned pale, texture is very soft, foul odor can be caused by bacteria. Coating method was using chitosan (CS) in an aerobic in order to preserve the fresh Pangasius sp. has been done in this study. Finding the best time preservation and influence of the degree of deacetylation of CS are purposes of this study. CS 1 and CS 2 were synthesized with difference of number of deacetylation. A number of CS was dissolved in acetic acid 1% to obtain 2.5% a solution of CS. The samples were soaked for 30 minutes in a solution of CS and then put in a plastic bag and stored for 12, 13, 14, 15, 16, and 17 hours. It were analyzed the amount of bacteria using the TPC method and organoleptic value. The results showed that the ability of antibacterial of CS 2 better than CS 1. The best time of preservation obtained at the 14th hour that was able to suppress the growth of bacteria while 7.103 col/g.